Rola mieszkań w socjalistycznym wzorcu konsumpcji i rozwoju społeczno-gospodarczym - Frąckowiak, Marian (Wydział Prawa i Administracji UAM, 1978)
Improvement of living conditions is a general aim of socialism. It represents humanistic contents of Marxism, for which ensuring high standard of material conditions of life is a fundamental assumption of all-round development of human personality. A particularly important role has been granted and it should be granted to flats in the socialist pattern of consumption, because possession of a flat is an indispensable condition of normal functioning and development of a fundamental social cell, which is constituted by a family. A siginificant improvement of housing situation in Poland contemporarily is not only a condition of happiness of many young families, of sizes of young generation, of its prosperity and education and the social development, but it also — conditioning improvements in professional qualification and general culture of the society — determines general rate of socio-economic growth of the country. Social functions of flats change visibly due to changes in the socio-economic level of country's development. Social needs on lower stages of the development are in principle satisfied by flats, enabling recovery of physical values of the society. On higher stages of the development a substantial improvement of housing situation is a condition of improvement of the society's professional knowledge and culture. Flats shape a sense of beauty and order. Disproportions between the number of working places in particular regions and housing resources cause an excessive staff fluctuation and a necessity of travelling to work from too far places. The role of flats in shaping market equilibrium is also worth of stress.
The Role of Flats in Socialist Pattern of Consumption and in Socio-Economic Development